Family Support Level For Independence Eye Defect Children In Sdlb Kemala Bhayangkari 1 Trenggalek - Eva Agustina Yalestyarini; Laili Wulandari (Journal of Health Science Community, 2023)
Self-reliance is the ability to overcome obstacles or problems on their own without the help of others. Independence will not grow by itself but in need of the efforts of each individual. Limitations of visual function causes the child has difficulty in developing the potential of the aspects of life. Without guidance and support, children with visual impairment will reach the difficulty in achieving the independence. The purpose of this study was to analyze the influence of family support for independence in SDLB Kemala Bhayangkari 1. The study design was cross-sectional. The sample of 30 respondents taken with random sampling method and using statistical test of Spearman rho. The independent variable is the support of family, the dependent variable is the independence of eye defect children.The results of the 30 respondents largely support families of eye defect children have high criteria, as many as 16 respondents (53%), and the independence of eye defect children have less independent criteria, a total of 17 respondents (45%).From the statistical test results obtained sig (2- tailed) of 0.002 <0.05 ,it can be concluded H1 accepted which means there is significant influence between Independence Family Support for Children with Visual Impairment In SDLB Kemala Bhayangkari 1 Psychology.Family support that the parents can increase the independence of eye defect children. This is because the support can cause the individual who receives the support he was able to build respect, trust, and feel valued that make children able to manage all its own, and can do things on their own without the help of others.